URGENSI BIMBINGAN KONSELING ISLAM DALAM MEMBENTUK MENTAL YANG SEHAT - Maslina Daulay (IAIN Padangsidimpuan, 2018)
The counseling guidance of Islam needs to be understood by every individual. If one can understand and can be applied the meaning of counseling guidance of Islam in his life, then someone has been able to reduce mental disorders experienced, so that the ultimate goal of the counseling guidance of Islam is to get happiness in the world and happiness in the hereafter. The counseling guidance of Islam can form a person free from the symptoms of psychiatric disorders, strive to meet environmental guidance without reducing self-esteem, can enable the potential psychological qualities that are typical of human beings, and apply religious guidance in life.